Vloga visokošolskega knjižničarja pri informacijski pismenosti doktorandov tehnike - primer gradbeništva - Koler-Povh, Teja (Knjižnica, 2018)
After the reform of the doctoral study programme in 2009 at the authors' faculty, an introductory course on scientific research methods became mandatory. It includes the topic of including information literacy (IL) and covers all its five main points according to ACRL 2000 standards. A librarian/researcher runs the practical part. After this course has been running for seven years we were interested in its impacts: (1) what are students' subjective impressions about the course and (2) how such a systematic education on IL topics objectively impacts their publishing and citations. The paper first presents the results of the questionnaire distributed among 120 PhD students who attended the program. The survey was conducted immediately after the completion of the IL course in the period 2009-2016. Four indicators were measured to address question (1): relevance, usefulness, complexity, and compliance with expectations. Question (2) studied by examining students' citation practices in their own PhD theses and their publishing results. The hypothesis was that the IL course increased students% competences. The students, who finished their dissertations in the period 2013%2016 September were divided in two groups, pre-Bologna and Bologna students. The quantitative parameters as the number of references in PhD theses and the number of scientific publications written during the study and shortly after it were measured. The hypothesis, that Bologna students cited more references in their dissertations and published more scientific publications were confirmed, with small differences between the groups. We conclude that the academic librarian contribute to the student's competences for their research work through his professional knowledge, skills and experiences.
Keywords: informacijska pismenost; raziskave; strokovna usposobljenost; študenti; visokošolske knjižnice; visokošolski knjižničarji